Immigration and Intergenerational Mobility in Metropolitan Los Angeles (IIMMLA), 2004 - Rumbaut, Rubén G. ([Verlag nicht ermittelbar], 2008)
IIMMLA was supported by the Russell Sage Foundation. Since 1991, the Russell Sage Foundation has funded a program of research aimed at assessing how well the young adult offspring of recent immigrants are faring as they move through American schools and into the labor market. Two previous major studies have begun to tell us about the paths to incorporation of the children of contemporary immigrants: The Children of Immigrants Longitudinal Study (CILS), and the Immigrant Second Generation in New York study. The Immigration and Intergenerational Mobility in Metropolitan Los Angeles study is the third major initiative analyzing the progress of the new second generation in the United States. The Immigration and Intergenerational Mobility in Metropolitan Los Angeles (IIMMLA) study focused on young adult children of immigrants (1.5- and second-generation) in greater Los Angeles. IIMMLA investigated mobility among young adult (ages 20-39) children of immigrants in metropolitan Los Angeles and, in the case of the Mexican-origin population there, among young adult members of the third- or later generations. The five-county Los Angeles metropolitan area (Los Angeles, Orange, Ventura, Riverside and San Bernardino counties) contains the largest concentrations of Mexicans, Salvadorans, Guatemalans, Filipinos, Chinese, Vietnamese, Koreans, and other nationalities in the United States. The diverse migration histories and modes of incorporation of these groups made the Los Angeles metropolitan area a strategic choice for a comparison study of the pathways of immigrant incorporation and mobility from one generation to the next. The IIMMLA study compared six foreign-born (1.5-generation) and foreign-parentage (second-generation) groups (Mexicans, Vietnamese, Filipinos, Koreans, Chinese, and Central Americans from Guatemala and El Salvador) with three native-born and native-parentage comparison groups (third- or later-generation Mexican Americans, and non-Hispanic Whites and Blacks). The targeted groups represent both the diversity of modes of incorporation in the United States and the range of occupational backgrounds and immigration status among contemporary immigrants (from professionals and entrepreneurs to laborers, refugees, and unauthorized migrants). The surveys provide basic demographic information as well as extensive data about socio-cultural orientation and mobility (e.g., language use, ethnic identity, religion, remittances, intermarriage, experiences of discrimination), economic mobility (e.g., parents' background, respondents' education, first and current job, wealth and income, encounters with the law), geographic mobility (childhood and present neighborhood of residence), and civic engagement and politics (political attitudes, voting behavior, as well as naturalization and transnational ties).